The chocolate bunny brouhaha - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2016)
"From the national bestselling author of The Chocolate Falcon Fraud comes an Easter-candy caper featuring chocolatiers Lee Woodyard and her aunt Nettie, and a killer who's hopping mad ... The approach of Easter means a rush of business at TenHuis Chocolade, and Lee and her aunt Nettie need all the help they can get to make their famous chocolate bunnies and eggs. Unfortunately, new hire Bunny Birdsong is a klutzy basket case, dropping everything she picks up. But to Lee's surprise, she's a wiz with computers and fixing the store's Web site so they decide to keep her. However, Bunny receives a few visitors they could do without: Her ex-husband, Beau; his wealthy aunt Abigail; and his new girlfriend and her brother all descend on the shop one day and have a bitter argument. Lee hopes they can find a peaceful way to settle their dispute and not bring any more trouble to TenHuis. But when Abigail's body is discovered in the vacant store next door, it's clear to Lee there's a bad egg in her midst. Now she's on the hunt to find out who it is.."--